Influencia de la diversidad y estructura arbórea sobre la regeneración natural en el bosque seco tropical de la reserva ecológica Arenillas (REA) - Quishpe Pinzón, Dalton Enrique (2015)
The structure of forests in general, is directly influenced by the intervention of internal and external factors that affect them directly and indirectly in the establishment or restoration of natural regeneration. In the Arenillas Ecological Reserve (AER), located in the cantons Arenillas and Huaquillas, in the Province El Oro, a plot of 9 ha permanent monitoring was established, which was established in 2011 under the project "Tropical Forests of the Equatorial dry Pacific region: diversity, structure, operation and conservation implications” where the relationship between the structure and diversity of tree layer on natural regeneration was studied. This monitoring area is subdivided into 225 sub plots of 20x 20m, of which 42 subplots 8 m2 in diameter for the lifting of regeneration, the same were selected systematically, trying to cover as much area as possible were selected; for the tree layer was used the preexisting information of the permanent plot, the same subplots which were used for regeneration, which was remeasured in 2014. The analyses were performed using generalized linear models in the statistical program R project (R Core Team, 2013), using the "glm" function; while the similarity was estimated using Pearson correlation index. All the analyzes were performed with a significance level of α = 0,05 With those data, the similarity of the structure and floristic composition of the tree layer with natural regeneration was analyzed; also the influence of the tree structure (richness, abundance, basal area and coverage) with the richness and abundance of natural regeneration was determined. In the floristic similarity of the two stratas (arboreal and natural regeneration), generally, it was observed that no significant linear relationship between the variables of the tree stratum and natural regeneration variables. Slight association was evident between the wealth of regeneration and abundance; the same way a slight association between the wealth of trees and abundance of natural regeneration. However, if it is considered an α = 0,1, the abundance of regeneration with the abundance of trees, if they have a good correlation because p value is 0,0809, also should be considered in studies of ecology a value of estimator 0,2724 is representative, because it is being evaluated under normal ambient conditions , so by comparing the value of the estimator 0,1089 wealth of regeneration and the abundance of trees , where a slight association is evidenced by a degree of α = 0,05. The similarity in the floristic composition is very similar, as in the community of dry forest, the tree layer consists of 15 species and 14 genders distributed in nine families, where the most representative botanical family is Fabaceae with 4 genders. While natural regeneration is represented by 10 families and 11 genders including 15 species, being the most representative Capparaceae and Fabaceae families with three genders respectively. On the influence of the tree structure on the abundance of regeneration, it was defined that the wealth and abundance of tree layer affects directly the abundance of natural regeneration individuals’ form. That is, in the dry forest community places where there is a greater number of tree species or individuals are associated with a high abundance of individuals belonging to natural regeneration. While the influence of the tree structure on the wealth of regeneration no relationship was evident, so apparently these are two separate processes.